2018
DOI: 10.1007/s12325-018-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Pharmacokinetic Study of Cysteamine Bitartrate Delayed-Release Capsules Following Oral Administration with Orange Juice, Water, or Omeprazole in Cystinosis

Abstract: IntroductionCystinosis is a rare, metabolic, autosomal recessive, genetic lysosomal storage disorder characterized by an accumulation of cystine in various organs and tissues. Cysteamine bitartrate (CB) is a cystine-depleting aminothiol agent approved in the United States and Europe in immediate-release and delayed-release (DR) formulations for the treatment of nephropathic cystinosis in children and adults. It is recommended that CBDR be administered with fruit juice (except grapefruit juice) for maximum abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
3
2
Order By: Relevance
“…This value was slightly higher than the peak concentration reported in a phase I pharmacokinetic study on cysteamine bitartrate conducted in adult patients (Cmax range: 1700.0-2000.0 ng/mL) [35]. However, in study by Armas D. and colleagues, the use of delayed-release capsules of cysteamine bitartrate produced a mean Tmax between 2.50 and 3.50 h [35]. Therefore, the use of a different oral formulation could partially explain the difference observed in our Cmax values.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This value was slightly higher than the peak concentration reported in a phase I pharmacokinetic study on cysteamine bitartrate conducted in adult patients (Cmax range: 1700.0-2000.0 ng/mL) [35]. However, in study by Armas D. and colleagues, the use of delayed-release capsules of cysteamine bitartrate produced a mean Tmax between 2.50 and 3.50 h [35]. Therefore, the use of a different oral formulation could partially explain the difference observed in our Cmax values.…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, in our study, the median cysteamine concentration for Cmax (post-dose) was 28.00 µM (IQR: 17.62-36.61), corresponding to 2160.20 ng/mL. This value was slightly higher than the peak concentration reported in a phase I pharmacokinetic study on cysteamine bitartrate conducted in adult patients (Cmax range: 1700.0-2000.0 ng/mL) [35]. However, in study by Armas D. and colleagues, the use of delayed-release capsules of cysteamine bitartrate produced a mean Tmax between 2.50 and 3.50 h [35].…”
Section: Discussioncontrasting
confidence: 43%
“…New Formulations of Cysteamine Cystagon, an immediate-release formulation of cysteamine and the first available treatment for cystinosis, was approved by the FDA in 1994. Although Cystagon effectively lowers cystine levels, it is associated with significant gastrointestinal symptoms (due to gastrin release and acid hypersecretion, which is alleviated by treatment with concomitant proton pump inhibitors [62]) and unpleasant sulfuric body and breath odor [63]. These side effects together with a strict dosing schedule (every 6 hours) substantially influence patients' adherence to treatment and can contribute to compromised clinical outcomes [63].…”
Section: New Emerging Therapiesmentioning
confidence: 99%
“…These side effects together with a strict dosing schedule (every 6 hours) substantially influence patients' adherence to treatment and can contribute to compromised clinical outcomes [63]. Procysbi, a delayed-release formulation of cysteamine bitartrate, bypasses the stomach and has sustained absorption in the small intestine, resulting in reduced gastrointestinal side effects [62,64]. In addition, it requires only a twice-daily dosing and thereby significantly improves the patient's quality of life by relieving the burdens of interrupted sleep for nighttime dosing [64,65].…”
Section: New Emerging Therapiesmentioning
confidence: 99%
“…Armas et al. [ 84 ] showed that the pharmacokinetics of cys bitartrate delayed-release capsules are not affected by co-administration with orange juice, water only, or omeprazole (with water).…”
Section: Pharmacokinetics Of Cysmentioning
confidence: 99%